WEBSITE APPLICATION PLANS FOR PROMOSION IDOESOFA SHOP USING PHP, MySQL, AND MACROMEDIA DREAMWEAFER 8.0 - Ade widodo; Munich Heindari Ekasari (Jurnal Sistem Informasi, 2010)
in information tecnologhy development grow fast in fact, so easy thateveryone getting some information. Information getting various, specially inworld sofa seller. Because of that, with this website the customer so easy gettingcome information about sofa seller and the kinds of sofa we cured.